Organic Fertilizer from Silk Tree litter (Albizia falcataria L.) to Enhance Magnesium Availability for Paddy (Oryza sativa L.) in Alfisol - Supriyadi Supriyadi; Dwi Priyo Ariyanto; Arlin Santoso (Faculty of Agriculture, Universitas Sebelas Maret, 2015)
The research had been done in Pereng, Mojogedang, Karanganyar. The aim of the research is to know the influence of organic fertilizer enrichment with the addition of Silk Tree litter (Albizia falcataria L.) to improve the availability and the uptake of Mg on the paddy (Oryza sativa L.) fields in Alfisol. The research used Complete Randomized Block Design (CRBD) with two factors that were dose treatments and cultivation systems. The data analysis used F test, Kruskal-Wallis test, DMRT test, Mood Median test, and correlation test at the 5% significance level. The results of the research showed that the availability and uptake of Mg in conventional cultivation system are higher than the SRI cultivation system. Mg uptake in conventional cultivation systems amount to 0.015 g/plant. The highest Mg availability can be achieved in the D6B1 treatment (50% organic fertilizer + 100% dose recommendation + Silk Tree litter amount 15% of the weight organic fertilizer) amount to 2.34 cmol(+)/kg. Organic fertilizer with the addition of Silk Tree litter cannot enrich the availability and uptake of Mg, but conventional cultivation systems can influence the availability and uptake of Mg. Conventional cultivation systems influencing the availability and uptake of Mg are higher than the SRI cultivation system.